2020
DOI: 10.1186/s12964-020-00533-w
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin promotes endothelial–mesenchymal transition during stress-induced premature senescence through the activation of autophagy

Abstract: Background: Rapamycin is known to be effective in suppressing senescence and the senescence-associated secretory phenotype (SASP). Therefore, it is highly expected to represent an anti-aging drug. Its anti-aging effect has been demonstrated at the mouse individual level. However, there are not many clinical findings with respect to its activity in humans. Here, we aimed to clarify the effect of rapamycin on human endothelial cells (ECs) as an in vitro model of human blood vessels. Methods: Over the course of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 63 publications
(68 reference statements)
1
22
0
Order By: Relevance
“…Several studies suggested that autophagy inhibition could induce EMT and fibrosis by affecting the aberrant epithelial–fibroblast crosstalk in idiopathic pulmonary fibrosis ( 21 ). Others showed that Rapamycin promotes EndMT through the activation of autophagy during premature senescence ( 22 ). ATG16L gene mainly includes ATG16L1 and ATG16L2.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that autophagy inhibition could induce EMT and fibrosis by affecting the aberrant epithelial–fibroblast crosstalk in idiopathic pulmonary fibrosis ( 21 ). Others showed that Rapamycin promotes EndMT through the activation of autophagy during premature senescence ( 22 ). ATG16L gene mainly includes ATG16L1 and ATG16L2.…”
Section: Introductionmentioning
confidence: 99%
“…10 Pharmacological inhibition of autophagy or small interfering RNA (siRNA) for ATG5-induced EndoMT. 4,11 Metabolic changes that rely on autophagy impairment drive endothelial phenotypic differentiation. In general, ECs tend to utilize aerobic glycolysis metabolism to survive, even under ample oxygen conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, cells acquire myofibroblast‐like characteristics with contractile function, enhanced migratory phenotypes, and increased extracellular matrix production 10 . Pharmacological inhibition of autophagy or small interfering RNA (siRNA) for ATG5‐induced EndoMT 4,11 . Metabolic changes that rely on autophagy impairment drive endothelial phenotypic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin inhibits the SASP by downregulating IL-6, IL-8, monocytes, chemotactic proteins, etc. [ 74 , 169 ]. Flavonoid 4,4′dimethoxychalcone (DMC) is considered an antiaging compound that has regulate the SASPs effects in mice and promotes autophagy through a pathway that involves specific GATA transcription factors [ 170 ].…”
Section: Treatment Strategies Targeting Senescencementioning
confidence: 99%